Implementation of the CTL (Contextual, Teaching, and Learning) Learning Model to Instill Religious and Socially Caring Characters in Class IIIA Students at Mojosongo III Elementary School, Surakarta - Nanda Rossy Pratiwi; Sutoyo Sutoyo; Mukhlis Mustofa (al-Afkar, Journal For Islamic Studies, 2026)
This study aims to describe the implementation of the Contextual Teaching and Learning (CTL) model in instilling religious and social care character among third-grade students at SD Negeri Mojosongo III Surakarta. The research employed a qualitative approach with a case study design. Data were collected through observation, interviews, and documentation. The findings indicate that the teacher implemented most CTL syntax, including constructivism, inquiry, questioning, and learning community. However, reflection and authentic assessment components were not fully applied. Religious character was developed through daily prayers, teacher role modeling, and integration of values such as honesty and responsibility. Social care character was fostered through group work, sharing habits, and simple social activities in class. Supporting factors included a strong school culture, teacher commitment, and parental involvement. Constraints included limited teacher understanding of all CTL syntax, restricted instructional time, and lack of contextual learning media. The study concludes that the CTL model is effective in character development when applied contextually, but its success depends on teacher training, institutional support, and collaboration between school and family.